Seroprevalence of IgG antibodies against diphtheria antitoxin among migrant workers in Singapore, 2016-2019 - Li Wei Ang; Qi Gao; Lin Cui; Aysha Farwin; Matthias Paul Han Sim Toh; Irving Charles Boudville; Mark I-Cheng Chen; Angela Chow; Raymond Tzer-Pin Lin; Vernon Jian Ming Lee; Yee Sin Leo (BMC, 2022)
Abstract Background Since the last local case of diphtheria in 1992, there had not been any case in Singapore until an autochthonous case was reported in 2017. This fatal diphtheria case of a migrant worker raised concerns about the potential re-emergence of locally transmitted toxigenic diphtheria in Singapore. We conducted a seroprevalence study to assess the immunity levels to diphtheria among migrant workers in Singapore. Methods Residual sera from migrant workers who hailed from Bangladesh, China, India, Indonesia, Malaysia, Myanmar and the Philippines were tested for anti-diphtheria toxoid immunoglobulin G (IgG) antibodies. These migrant workers previously participated in a survey between 2016 and 2019 and had provided blood samples as part of the survey procedure. Results A total of 2176 migrant workers were included in the study. Their overall mean age was 27.1 years (standard deviation 5.0), range was 20-43 years. The proportion having at least basic protection against diphtheria (antitoxin titres ≥ 0.01 IU/ml) ranged from 77.9% (95% confidence interval [CI] 72.8 - 82.3%) among migrant workers from Bangladesh to 96.7% (95% CI 92.5 - 98.6%) in those hailing from Malaysia. The proportion showing full protection (antitoxin titres ≥ 0.10 IU/ml) ranged from 10.1% (95% CI 6.5 - 15.4%) in Chinese workers to 23.0% (95% CI 17.1 - 30.3%) in Malaysian workers. There were no significant differences in the proportion with at least basic protection across birth cohorts, except for those from Bangladesh where the seroprevalence was significantly lower in younger migrant workers born after 1989. Conclusions The proportions having at least basic protection against diphtheria in migrant workers from five out of seven Asian countries (India, Indonesia, Malaysia, Myanmar and the Philippines) were higher than 85%, the threshold for diphtheria herd immunity. Seroprevalence surveys should be conducted periodically to assess the level of immunity against diphtheria and other vaccine preventable diseases in migrant worker population, so that appropriate interventions such as booster vaccination can be implemented proactively to prevent sporadic outbreaks.